PENGECUALIAN ASAS LEGALITAS DALAM HUKUM PIDANA - Weda, Made Darma (Jurnal Hukum dan Peradilan, 2013)
Debating for exceptional of legality principle in criminal law could be learned by establishing of the International Criminal Tribunal for The Farmer Yugoslavia (ICTY) which was based on United Nation‟s Resolution in 1993, No. 827 and The International Criminal Tribunal for the Rwanda (ICTR) which was based on United Nation‟s Resolution in 1994, No. 955. Even though these tribunals were rejected by the parties who supported the dependents, they still to cross-examine those cases, even though it was against the principle of nullum crimen sine lege as retroactive principe in criminal law. Keywords: Retroactive, criminal law, exceptional.